Gandhian way : peace, non-violence, and empowerment - Sharma, Anand; International Conference on Peace, Non-violence, and Empowerment: Gandhian Philosophy in the 21st century (2007 : New Delhi, India) (New Delhi : Academic Foundations, 2007)
Indian National Congress
Keywords: Gandhi, Mahatma -- 1869-1948 -- Philosophy; Passive resistance -- Congresses